Focused classroom meeting model of teaching for enhancing students’ achievement motivation - Edy Purwanto; Sunawan Sunawan (LPMPP Universitas Negeri Yogyakarta, 2022)
There have been different models of achievement motivation models proposed in the literature. This article aims to examine the effectiveness of the Focused Classroom Meeting Model of Teaching (FCMMT) which is based on the Trisula Model of Achievement Motivation in English as a foreign language setting. The effectiveness of FCMMT was examined through experimental research with randomized pre-test post-test control group design. The subjects consisted of 40 students of 11th Grade who were randomly selected from a senior high school. They were, then, randomly assigned into two different groups, namely experimental and control groups. The experimental group received FCMMT of teaching model intervention, while the control group was given classroom management intervention by applying the experimental design of the control group pre-test multiple post-tests. Both experimental and control groups received teaching intervention for 12 sessions (90 minutes per session; twice per week). The achievement motivation scale used was adapted from the Motivated Strategies for Learning Questionnaire (MSLQ). The result of the experiment showed that FCMMT was effective in enhancing students’ achievement motivation. This study provides an alternative new model empirically found effective for increasing student achievement motivation, namely task value, self-efficacy, and goal orientation.